Clearing the Hurdle of Corruption: Indonesia’s Path to OECD Accession - Cason, Christopher Michael; Hefni, Hanna Adistyana (Jambe Law Journal, 2024)
Indonesia has recently entered into formal talks with the Organization for Economic Cooperation and Development (OECD).  While debate persists about the wisdom of such a move, it is relevant to recognize that there are many hurdles to overcome. The OECD has provided Indonesia a roadmap outlining both procedures and substantive legislative provisions required for accession to the OECD treaty.  Among these requirements,  OECD membership candidates must establish law that are in compliance with the OECD Anti-Bribery Convention.  Given Indonesia’s history, this component may pose a significant impediment to OECD membership.  To explore this, the study examines the accession path of other recent members to the OECD and provides guidance for clear changes that are required to Indonesia’s legal framework surrounding corruption.  This study found that compliance with the OECD Anti-Bribery Convention as imperative, as demonstrated by the experiences of countries that have recently joined the OECD and other candidate countries that are further along in the accession process than Indonesia.  This research also demonstrates that significant legislative changes to Indonesia’s legal framework on corruption are required for full accession to the OECD Convention